ANALOGY OF THE TEACHING OF MUSIC AND ORAL LANGUAGE: IT’S APLICATION IN THE TEACHING OF GUITAR - Piedra Navarro, Ivis Nancy; Vázquez Pérez, Hanoi (Atenas, 2013)
The exigencies of urgent formation for preschool educators impose the searching of alternatives that facilitate the achievements of the objectives. This constitutes the premise that led us to deepen on the specific particularities of the process of initiating in the teaching of music and oral language for determining the elements that facilitate the learning of the guitar. For this, it is taken into account the contents, that in this respect, the syllabus of Musical Training and Guitar proposes to be taught.